(untitled) (Baghdad Science Journal, 2020)
This study is pointed out to estimate the effectiveness of two solvents in the extraction and evaluating the active ingredients and their antioxidant activity as well as anti-cancer efficiency. Therefore, residues from four different Brassica vegetables viz. broccoli, Brussels sprout, cauliflower, and red cherry radish were extracted using two procedures methods: methanolic and water crude extracts. Methanol extracts showed the highest content of total phenolic (TP), total flavonoids (TF), and total tannins (TT) for broccoli and Brussels sprouts residues. Methanolic extract of broccoli and Brussels sprouts residues showed the highest DPPH· scavenging activity (IC50 = 15.39 and 18.64 µg/ml). The methanol and water extracts of Brussels sprout residues showed the highest chelating activity (IC50 = 11.77 and 5.94 µg/ml) and exhibited the highest reducing power (EC50 =14.38 and 20.18 µg/ml) with broccoli respectively. The HPLC analysis of phenolic compounds confirmed that the methanol extract of all the residues examined possessed high amounts of catchine, rutin, cumaric, benzoic, and luteolin. The methanol extract at 100 µg/ml of Brussels sprouts residues displayed a rise cytotoxic effect on HePG2 (80.40%), MCF7 (75.49%) and HCT116 (22.74%) followed by broccoli and red cherry radish, respectively. This result confirmed that Brussels sprouts residue contain effective chemical compounds that can inhibit the proliferation of cancer cells. Therefore, these results proposed that those Brassica vegetable residues might be beneficial as a potent antioxidant and anticancer agents and strongly recommended as fixing in constituent’s food applications and pharmaceutical industries.